Desain Taman Kupu-Kupu Sebagai Pengembangan Perkebunan Kelapa Sawit Berbasis Konservasi Berkelanjutan di Tangkahan Sumatera Utara - Simbolon, Refinna; Irni, Julaili (JURNAL AGROPLASMA, 2025)
This study reveals that the development of a butterfly garden as a post-oil palm plantation land use strategy in Tangkahan holds significant ecological and social potential. Observations indicate a clear difference in butterfly species composition between the garden area and the former plantation, with a moderate diversity index and low similarity index. These findings underscore the importance of mosaic habitat management to enhance species diversity. Several host and nectar plants were identified, including Citrus sp., Ageratum conyzoides, Chromolaena odorata, and Lantana camara, which support a lifecycle-based garden design. Community perception was generally positive, and chi-square analysis showed that public support transcended age, education, and occupation. The garden is zoned into three key areas: conservation core, education zone, and buffer zone, covering a 100 x 100 meter area. With construction progress reaching 40%, the integration of ecological and social elements must continue to ensure long-term sustainability of conservation efforts in the region. Keywords: butterfly garden, biodiversity, sutainable conservative, garden zoning, host and nectar planting